Investigations Concerning the Syntheses of TADDOL-Derived Secondary Amines and Their Use To Access Novel Chiral Organocatalysts - Gratzer, Katharina; Waser, Mario (Synthesis, 2012)
A structurally carefully diversified library of novel TADDOL-derived chiral secondary amines was synthesized and investigated for their applicability to obtain new organocatalysts like chiral Lewis bases and chiral phase-transfer catalysts. The scope and limitations of the developed syntheses routes to access these catalysts as well their catalytic performance in different benchmark reactions were systematically investigated. The most powerful of the catalysts prepared was found to be highly useful for the phase-transfer catalyzed α-alkylation of glycine Schiff base (high yields and up to 93% ee).
Keywords: chiral pool; tartaric acid; asymmetric phase-transfer catalysis; Lewis base catalysis; asymmetric alkylation